School Trip - Craft, Jerry (New York : Quill Tree Books/Harper Alley, imprints of HarperCollinsPublishers, 2023)
Jordan, Drew, Liam, Maury, and their friends from Riverdale Academy Day School are heading out on a school trip to Paris. As an aspiring artist himself, Jordan can't wait to see all the amazing art in the famous City of Lights. But when their trusted faculty guides are replaced at the last minute, the school trip takes an unexpected--and hilarious--turn. Especially when trying to find their way around a foreign city ends up being almost as tricky as navigating the same friendships, fears, and differences that they struggle with at home.
Keywords: African American boys -- Comic books, strips, etc; Middle school students -- Comic books, strips, etc; Voyages and travels -- Comic books, strips, etc; School field trips -- Comic books, strips, etc; Young artists -- Comic books, strips, etc; Americans -- Comic books, strips, etc. -- France; Friendship -- Comic books, strips, etc; African American boys -- Fiction; Middle school students -- Fiction; Voyages and travels -- Fiction; School field trips -- Fiction; Young artists -- Fiction; Americans -- Fiction. -- France; Friendship -- Fiction; Cartoons and comics; Paris (France) -- Comic books, strips, etc; Paris (France) -- Fiction; Comics (Graphic works); Graphic novels